2012
DOI: 10.1038/nchembio.975
|View full text |Cite
|
Sign up to set email alerts
|

Natural strategies for the spatial optimization of metabolism in synthetic biology

Abstract: Metabolism is a highly interconnected web of chemical reactions that power life. Though the stoichiometry of metabolism is well understood, the multidimensional aspects of metabolic regulation in time and space remain difficult to define, model and engineer. Complex metabolic conversions can be performed by multiple species working cooperatively and exchanging metabolites via structured networks of organisms and resources. Within cells, metabolism is spatially regulated via sequestration in subcellular compart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
284
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 361 publications
(287 citation statements)
references
References 100 publications
0
284
0
3
Order By: Relevance
“…However, previous research on microbial consortia was primarily concerned with the study of mixed population stability and dynamic interactions (7)(8)(9)(10)(11), although a few recent studies have reported the engineering of microbial consortia for utilization of simple sugars to make small molecules of central carbon metabolism, such as ethanol and lactate (12,13). Progress was made recently, when a full n-butanol pathway was expressed in two separate E. coli cells to achieve higher production (14) and when a bacterium-yeast coculture was used to address the difficulties of functional reconstitution of a pathway involving prokaryotic and eukaryotic enzymes in a consortium, and thus improved production of complex pharmaceutical molecules (15).…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…However, previous research on microbial consortia was primarily concerned with the study of mixed population stability and dynamic interactions (7)(8)(9)(10)(11), although a few recent studies have reported the engineering of microbial consortia for utilization of simple sugars to make small molecules of central carbon metabolism, such as ethanol and lactate (12,13). Progress was made recently, when a full n-butanol pathway was expressed in two separate E. coli cells to achieve higher production (14) and when a bacterium-yeast coculture was used to address the difficulties of functional reconstitution of a pathway involving prokaryotic and eukaryotic enzymes in a consortium, and thus improved production of complex pharmaceutical molecules (15).…”
Section: -Hydroxybenzoic Acidmentioning
confidence: 99%
“…To increase the overall reaction efficiency, a spatiotemporal control of the intermediate product is essential. 30 A cellular system optimizes the compartmentalization of metabolic pathways to reduce any significant loss of an intermediate product.…”
Section: Test Of the Microreactorsmentioning
confidence: 99%
“…41 The high level of spatial organization and integration enables the metabolism to be an optimized network of interconnected biological reactions that guide the production, transportation and consumption of nutrients and allows for the maintenance, growth and reproduction of life. Inspired by nature, synthetic biologists are aiming to build biomimetic nano/microfactories for the positional immobilization of multienzymatic cascades with nanoscale precision.…”
Section: Regulating Reaction Pathways For Bioinspired Nanofactoriesmentioning
confidence: 99%